Distribution of Salmonella virulence factors originated from sheep and cattle in Algerian slaughterhouses - Nouichi, S; Mezali, L; Hamdi, TM (Journal of the Hellenic Veterinary Medical Society, 2023)
The present study was carried out to determine the virulence gene profiles associated with Salmonella subsp. enterica strains recovered from cattle and sheep samples by polymerase chain reaction (PCR). A total of 84 Salmonella isolates belonging to 10 serovars were screened for presence of 8 different virulence genes (invA, pefA, sefA, pipB, sseC, ssaP, spvC and iroB) using their specific primers. Different distribution patterns of these genes were noticed amongst the isolates. While the iroB gene was the most identified (n= 65, 77.4%), the sefA gene was not detected in all tested strains. pefA and spvC genes were detected in S. Typhimurium only with a rate of 3.6%. The four other genes were found to be present in 61.9% each. Occurrence of virulence genes did not vary significantly (P> 0.05) by serovar or animal species, neither by type of sample. The presence of all screened genes was significantly associated with resistance to at least one antibiotic from different classes except quinolones. These results show that transmissible pathogenic Salmonella strains are circulating in slaughterhouses in Algeria.